Saving children from a life of crime early risk factors and effective interventions - Farrington, David P.; Welsh, Brandon, 1969- (New York ; Oxford : Oxford University Press, 2007)
After decades of rigorous study in the United States and across the Western world, a great deal is known about the early risk factors for offending. High impulsiveness, low attainment, criminal parents, parental conflict, and growing up in a deprived, high-crime neighborhood are among the most important factors. There is also a growing body of high quality scientific evidence on the effectiveness of early prevention programs designed to prevent children from embarking on a life of crime. Drawing on the latest evidence, this title assesses the early causes of offending and what works best to prevent it.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Juvenile delinquency -- United States -- Prevention